Gluten-free cereal products and beverages: a review of their health benefits in the last five years - Khairuddin, Muhammad Arif Najmi; Lasekan, Ola (Multidisciplinary Digital Publishing Institute, 2021)
In the past decades, food products and beverages made from gluten-free cereals were initially created for certain groups of people who experience gluten-related disorders such as wheat allergies, gluten ataxia, non-celiac gluten sensitivity, and the most well-known, celiac disease. Nowadays, the consumption of gluten-free products is not only restricted to targeted groups, but it has become a food trend for normal consumers, especially in countries such as the UK, the US, and some European countries, who believe that consuming a gluten-free product is a healthier choice compared to normal gluten-containing products. However, some research studies have disapproved of this claim because the currently available gluten-free products in the market are generally known to be lower in proteins, vitamins, and minerals and to contain higher lipids, sugar, and salt compared to their gluten-containing counterparts. The use of other gluten-free cereals such as sorghum, millet, and teff as well as pseudo cereals such as buckwheat and quinoa has gained significant interest in research in terms of their various potential health benefits. Hence, this review highlights the potential health benefits of some gluten-free cereals and pseudo cereals apart from corn and rice in the last decade. The potential health benefits of gluten-free products such as bread, pasta, crackers, and cookies and the health benefits of some other non-alcoholic beverages made from gluten-free cereals and pseudo cereals are reported.